Integrated agricultural development real time analysis based on Internet of Things in Jenggawah Village - Widjonarko; Muh. Asnoer Laagu; Ali Rizal Chaidir; Muhamad Ali Yafi; Indra Viktorrisman (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Jenggawah Village, Jember Regency is a lowland area with great potential as an agricultural barn. However, the abundance of agricultural commodities has not been balanced with the application of modern technology, so that productivity is disrupted by conventional methods and unpredictable climate change. To overcome this, an integrated agricultural system based on the Internet of Things (IoT) was implemented through a real-time analysis method to predict climate and monitor land conditions. This program includes surveys, system design, installation of monitoring tools, and socialization of precision agricultural technology. This system uses five main sensors (soil moisture, light intensity, rainfall, wind speed, and air quality) connected to a mobile website, allowing farmers to monitor their land in real time. In testing, the monitoring tool recorded daily energy consumption of 136.32 Wh, supported by a 100 Wp solar panel and a 56.8 Ah battery. This program is accompanied by training and technology transfer to farmers to increase productivity, soft skills, and welfare. As a result, the community accepted the technology well, accelerated the digitalization of agriculture, and made Jenggawah Village a pilot model for the application of precision agricultural technology in other areas.